Microbiome profiling in extremely acidic soils affected by hydrothermal fluids: the case of the Solfatara Crater (Campi Flegrei, southern Italy). Issue 12 (21st September 2018) - Crognale, Simona; Venturi, Stefania; Tassi, Franco; Rossetti, Simona; Rashed, Heba; Cabassi, Jacopo; Capecchiacci, Francesco; Nisi, Barbara; Vaselli, Orlando; Morrison, Hilary G; Sogin, Mitchell L; Fazi, Stefano
ABSTRACT: An integrated geochemical and microbiological investigation of soils from the Solfatara Crater (Campi Flegrei, southern Italy) demonstrated that interstitial soil gases dominated by CO2 and other typical hydrothermal gaseous species (e.g. H2 S, CH4, ethane, benzene, alkenes and S-bearing organic compounds) influenced the composition of microbial communities. The relatively high concentrations of hydrothermal fluids permeating the soil produced acidic conditions and whitish deposits that characterize the Solfatara Crater floor. Archaea and Bacteria showed almost equal cell abundance (up to 3.2 × 10 7 and 4.2 × 10 7 cell/g, respectively) with relatively low levels of biodiversity and equitability in sites characterized by elevated temperatures (up to 70°C), very low pH values (up to 2.2) and reducing conditions. In these sites, high-throughput sequencing showed the marked selection of microorganisms, mainly affiliated with the genera Thermoplasma, Ferroplasma and Acidithiobacillus . A relatively high biodiversity and concomitant distinctive structure of the microbial community were observed in soils poorly affected by fumarolic emissions that were oxic and rich in organic matter. Abstract : The geochemical and microbiological characterization of extremely acidic soils from the Solfatara Crater highlighted how the microbial communities are shaped by deep-originated gases and elements.